Low-Temperature winemaking by thermally dried immobilized yeast on delignified brewer's spent grains - Tsaousi, Konstantina; Velli, Asimina; Akarepis, Filippos; Bosnea, Loulouda A.; Koutinas, Athanasios A.; Bekatorou, Argyro; Drouza, Chryssoula (My University, 2011)
Preservation, risk of contamination, transportation and storage costs (e.g. refrigeration) are the main problems associated with wet, active starter cultures such as yeast. To deal with these aspects, drying of commercial cultures is required. A thermally dried biocatalyst has been prepared by immobilization of the psychrotolerant yeast strain Saccharomyces cerevisiae AXAZ-1 on delignified brewer's spent grains, followed by simple thermal drying or by air stream at 30 and 35 °C. Repeated batch fermentations of grape must (11.5 °Be, corresponding to 196 g/L of fermentable sugar) using the dried biocatalysts were performed at successively reduced temperatures (15, 10 and 5 °C). The fermented samples were analyzed for residual sugar, alcohol and free cell concentrations. The alcohol yield, alcohol productivity and sugar conversion were calculated in order to estimate the optimum conditions of drying. The volatile constituents in the produced wines were analysed by GC analysis. The results showed that drying of immobilized cells by the proposed techniques did not affect their viability and fermentative activity. High alcohol productivity, increased esters and lower concentrations of higher alcohols obtained by low-temperature fermentation using the dried biocatalysts indicate a potential improvement of product quality
Keywords: Brewer's spent grains; Immobilization; Thermal drying; Winemaking